Cardiovascular rehabilitation in patients with mechanical valvular prosthesis - José Leandro Pérez Guerrero; William Arias Salazar; Odanis Monjes Aguero (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Heart rehabilitation in patients with valvular prosthesis is essential to increase their survival and incorporate them optimally to the society. Objective: To characterize patients with mechanical valvular prosthesis and cardiovascular rehabilitation. Methods: An observational, descriptive, serial cases study of 70 patients with mechanical valvular prosthesis was carried out, who were admitted to the program of cardiovascular rehabilitation of Vladimir Ilich Lenin University General Hospital in Holguín province, from March, 2019 to November, 2022. Results: There was a prevalence of 55 to 64 years patients (38.6%), with prosthesis in mitral position, without complications. In the rehabilitated patients a reduction of the mean in hypercholesterolemia was observed (from 250 to 175 mg/dL) and an increase of the functional capacity due to the duration of exercise, as well as of the consumed metabolic units. There was an increase from 52.4 to 58.2% in the mean of the left ventricular function after the rehabilitative therapy. Only 2 affected patients needed rehospitalization and to incorporate more medication to their basal treatment and 50 returned to their working activities. The result was satisfactory in 97.1% of the series members. Conclusions: This therapy was beneficial, because there was an increase of the functional capacity of patients and complications were not very common. The coronary risk factors were controlled; there was a reduction of rehospitalization and an increase of working reincorporation.